Antibacterial and Antifungal Evaluation of Chloroflavones (Journal of Scientific Research, 2018)
Two chloroflavones, 6 and 7 along with their corresponding chalcones, 4 and 5 have been tested for antibacterial and antifungal activities against six human pathogenic bacteria viz. Bacillus cereus (G+), Staphylococcus aureus (G+), Escherichia coli (G-), Vibrio choloriae (G-), Pseudomonas aeruginosa (G-), and Salmonella typhi (G-), and four plant as well as mold fungi viz. Aspergillus flavus, Aspergillus ochraceus, Aspergillus niger and Rhizopus spp.. The antibacterial and antifungal screens of the synthesized compounds were performed in vitro by the filter paper disc diffusion method and the poisoned food technique, respectively. The minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) of these synthesized compounds in comparison to ampicillin were also determined by broth micro-dilution method. Some of them were found to possess significant activity, when compared to standard drugs.